2016
DOI: 10.1158/1541-7786.mcr-15-0368
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Genomic Analyses Yield Cell-Cycle Regulatory Programs with Prognostic Value

Abstract: Liposarcoma is the second most common form of sarcoma, which has been categorized into four molecular subtypes, which are associated with differential prognosis of patients. However, the transcriptional regulatory programs associated with distinct histological and molecular subtypes of liposarcoma have not been investigated. This study uses integrative analyses to systematically define the transcriptional regulatory programs associated with liposarcoma. Likewise, computational methods are used to identify regu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…As shown, P53 targets only represent a small fraction (~4%) of the differentially expressed genes, suggesting that the majority of them are indirectly regulated by the P53 pathway. Additionally, according to our previous study, we provided the importance of using the indirect targets of transcriptional factor to estimate its pathway activity (48,49). Therefore, even though those P53 target genes were indirectly regulated by P53 pathway, it is reasonable to include them into P53 gene signature to enhance the power of statistical inference on P53 pathway activity for the future analysis.…”
Section: Resultsmentioning
confidence: 99%
“…As shown, P53 targets only represent a small fraction (~4%) of the differentially expressed genes, suggesting that the majority of them are indirectly regulated by the P53 pathway. Additionally, according to our previous study, we provided the importance of using the indirect targets of transcriptional factor to estimate its pathway activity (48,49). Therefore, even though those P53 target genes were indirectly regulated by P53 pathway, it is reasonable to include them into P53 gene signature to enhance the power of statistical inference on P53 pathway activity for the future analysis.…”
Section: Resultsmentioning
confidence: 99%
“…As a family of transcription factors, E2Fs play important roles in GC by modulating the transcription of specific target genes, and their regulatory activity and biological effects can be reflected by their target gene expression. It has been reported that high E2F1 or E2F4 activity in liposarcoma patients is associated with unfavorable prognosis, with the core target gene sets of E2F1 containing 116 genes and the core target gene sets of E2F4 containing 199 genes, among which only 21 are shared ( 30 ). As we have shown, GSEA indicated that E2F1 was mainly involved in the cell cycle pathway; E2F4 , however, was mainly involved in ribosome pathway.…”
Section: Discussionmentioning
confidence: 99%
“…We note that our methods are distinct from con dence prediction scores that models inherently have, because our con dence score considers the effect of clinical features. We use three multi-gene signatures, including Oncotype DX, MammaPrint and an E2F4 signature [20][21][22], to demonstrate the potential of this framework to change the way of biomarker application. We use these signatures to construct classi cation models to predict patient response to neoadjuvant (pCR vs. RD, residual disease), and Cox regression models to predict patient recurrence-free survival in breast cancer.…”
Section: Introductionmentioning
confidence: 99%